Analisis Nilai Moral dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Sarmila Sarmila (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to find the Analysis of Moral Values ​​in the Novel Surat Kecil Untuk Karya Agnes Davonar. This study discusses the Analysis of Moral Values ​​in the Novel Surat Kecil Untuk Karya Agnes Davonar. This research is a qualitative study. While data collection is done by reading and recording methods. From the results of the study, it can be seen that literature is the best written or printed work made by humans, creatures given reason. Humans are present to provide understanding related to what is conveyed through the medium of language. But sometimes just to understand, it needs to be studied specifically. understand the literature from a different perspective, namely moral. therefore the purpose of the following literary researchers is Moral Values ​​in the Novel Surat Kecil Untuk Karya Agnes Davonar. The research method used by researchers is descriptive qualitative. This study describes the object being studied by developing morals. Researchers act as the main instrument with the help of data. The data intended by this study is the moral data contained in the novel Surat Kecil Untuk Tuhan. And then used as a data source in the following research, namely the novel